POLITIK ANGGARAN DAN RELASI AKTOR DALAM PENYUSUNAN ANGGARAN PENDAPATAN BELANJA DAERAH - Hamka, Muh.; Nadir, Sakinah; Haryanto (Jurnal Politik Profetik, 2022)
The making of regional budgets involves several actors who have an interest in the Regional Revenue and Expenditure Budget (APBD). The relationship between each actor forms a structured and systematic network and arranges strategies to accommodate the interests of actors in the APBD. This article aims to explain how the relationship between actors and budget politics forms interests in the making of the APBD. The research method used is qualitative with a descriptive analysis type to describe the relationship of each actor by using actor-network theory and public policy. The results of the study found that the actors involved in the making of regional budgets were grouped into two, namely formal actors and informal actors. The main actors who dominate the making of regional budgets are the regional head as the highest decision holder and family relations as informal actors who influence decision making. Each actor forms a network to accommodate their interests in the APBD by strengthening their relationship with the highest decision-makers in regional budgeting. The strategy of actors in entering and guarding their interests in the APBD uses four political strategy frameworks, namely position strategy, power strategy, player strategy, and perception strategy. This article contributes to understanding that APBD budget politics cannot be separated from the role of formal actors and informal actors who have formed networks in guarding their respective interests.